(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
It is well-known that small businesses and private entrepreneurship, being inseparable elements of the modern market economy system, have publicly available market relations mechanisms that help the state establish relations with a large number of entrepreneurs, as well as encourage their initiative abilities. Also, the introduction of foreign investment in this sector of the economy will not only increase their efficiency but will also give an additional incentive to the development of entrepreneurship. Uzbekistan, at the crossroads of trade routes, has always been in the spotlight of foreign-language traders and entrepreneurs who have encouraged bilateral relations. This process can be traced to the present, when the initiative abilities of entrepreneurship were encouraged in every way by the state. These and other issues of the development of small business and private entrepreneurship in conjunction with the attraction of foreign capital in Uzbekistan are disclosed in this article.